2014
DOI: 10.7883/yoken.67.95
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study to Identify Environmental Risk Factors for Hand, Foot, and Mouth Disease Outbreaks in Beijing

Abstract: SUMMARY: A matched case-control study was conducted in Beijing to identify the relative importance of major environmental risk factors for outbreaks of hand, foot, and mouth disease (HFMD). A case was defined as a kindergarten class with at least 1 HFMD outbreak. As a control, a kindergarten class that did not experience an HFMD outbreak was used. To identify potential transmission factors, the control group was divided into 2 subgroups: a sporadic group and an HFMD-negative group. We collected data for 8 envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
(13 reference statements)
3
6
0
Order By: Relevance
“…Several proposed factors, including pathogen infectivity outside the host, human behavior, and immune function fluctuations, are involved in the seasonal patterns of infectious diseases [ 31 ], and these factors could also be responsible for the relationship between meteorological variations and HFMD. Our findings are generally in line with studies from different regions of Asia [ 15 17 , 21 28 ]. Our study found a positive association between temperature and HFMD, with increasing trends for mean temperatures between 8°C and 20°C and above 25°C and a plateau between 20°C and 25°C.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Several proposed factors, including pathogen infectivity outside the host, human behavior, and immune function fluctuations, are involved in the seasonal patterns of infectious diseases [ 31 ], and these factors could also be responsible for the relationship between meteorological variations and HFMD. Our findings are generally in line with studies from different regions of Asia [ 15 17 , 21 28 ]. Our study found a positive association between temperature and HFMD, with increasing trends for mean temperatures between 8°C and 20°C and above 25°C and a plateau between 20°C and 25°C.…”
Section: Discussionsupporting
confidence: 93%
“…Some vaccine-preventable infectious diseases, including Japanese encephalitis, yellow fever, influenza, rotavirus infection, hepatitis A virus infection and hepatitis B virus infection, were also found to be differentially influenced by ultraviolet radiation from the sun through modulating vector reproduction [ 40 ]. In addition, a preventive effect of indoor solar radiation on HFMD was presumed [ 21 ]. One plausible reason is that higher solar radiation could also cause temperatures at ground level in urban areas to be higher than temperatures measured at weather stations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several limitations of this study should be acknowledged. First, some major risk factors for HFMD disease including season, suburban, ultraviolet (UV) radiation, childhood aggregation, socio-economic status [ 34 ], as well as environmental factors such as temperature, PM 10 , and PM 2.5 should be considered together to adjust them in the models. We adjusted only the meteorological parameters and PM 10 in the model, which may have led to outcome bias, thus, the next step is to improve the statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers found that the incidence of HFMD might be associated with some environmental factors [ 14 , 24 , 31 , 51 , 52 , 53 , 54 , 55 , 56 ]. After analysis of the epidemiological features of HFMD in Mainland China during 2008–2012, Xin et al [ 14 ] indicated that evident geographical differences existed in the seasonal patterns of the incidence of HFMD between northern and southern China, and these differences were in weak associations with some climatic factors.…”
Section: Influencing Factorsmentioning
confidence: 99%